Left ventricular non-compaction cardiomyopathy and left ventricular assist device: a word of caution. Issue 1 (December 2016) - Kornberger, A.; Stock, U.; Risteski, P.; Beiras Fernandez, A.
Abstract Background In patients with left ventricular non-compaction (LVNC), implantation of a left ventricular assist device (LVAD) may be performed as a bridge to transplantation. In this respect, the particular characteristics of the left ventricular myocardium may represent a challenge. Case presentation We report a patient with LVNC who required urgent heart transplantation for inflow cannula obstruction nine months after receiving a LVAD. LVAD parameters, echocardiography and examination of the explanted heart suggested changes of left ventricular configuration brought about by LVAD support as the most likely cause of inflow cannula obstruction. Conclusions We conclude that changes experienced by non-compacted myocardium during LVAD support may give rise to inflow cannula obstruction and flow reduction. Presence of LVNC mandates tight surveillance for changes in LV configuration and LVAD flow characteristics and may justify urgent transplantation listing status.